PARADIGM AND SYMBOLIC UNIVERSE: THE ENDURING SIGNIFICANCE OF THOMAS KUHN (Annals of the University of Bucharest. Philosophy Series, 2024)
The importance of Kuhn’s theory is examined from the perspective of its epistemological impact and contrasted with Popper’s concept of falsification; the theory of paradigm shift is analyzed as a general model of change. Its concepts are applied to Berger and Luckmann’s socially constructed reality and to the Symbolic Universe which sustains it. The theory of paradigm shift is used to analyze the process of changing the Symbolic Universe.
Keywords: Paradigm; anomaly; incommensurability; Symbolic Universe; conspiracy theories; apophenia; crank magnetism; information bubble